Assessment of the validity of the AUDIT factor structure in parents involved with child protective services. (2nd September 2020) - Seay, Kristen D.; Feely, Megan
ABSTRACT: Background : Identification of hazardous alcohol use is a critical step in connecting individuals to treatment and child protective services (CPS) is a treatment entry-point for parents if hazardous use is identified. The Alcohol Use Disorders Identification Test (AUDIT) is a common screening tool in this setting. However, prior research identifies one to three factors in the AUDIT, revealing uncertainty in the perception and/or impact of alcohol use. Determining the factor structure of the AUDIT for CPS-involved parents is important for its relevance and use in CPS. Objectives : This analysis examines the type and number of factors present in a sample of parents involved with CPS. Methods : Using confirmatory factor analysis (CFA), this study compares the one-, two-, and three-factor structures of the AUDIT in a large sample of CPS-involved parents (N = 4009, 90.8% female, 9.2% male) and a sub-sample who endorsed alcohol use (N = 1950). This analysis used data from Waves I and II of the National Survey of Child and Adolescent Well-Being II. Results : In the main sample, the two-factor (RMSEA = .044, 90% CI: 0.039–0.048; CFI = 0.967; TLI = 0.956) and three-factor (RMSEA = .045, 90% CI: 0.041–0.050; CFI = 0.966; TLI = 0.952) fit better than the single factor model (RMSEA = .072, 90% CI: 0.067–0.076; CFI = 0.908; TLI = 0.881). In the three-factor model two of the factors had a correlation of 0.99; parsimonious models are usually preferable. Sub-sample results were similar. Conclusions : The two-factor AUDIT is appropriate for screening CPS-involved parents. Screening with the AUDIT should improve early identification and referral to treatment for CPS-involved parents with hazardous alcohol use.